2003
DOI: 10.1172/jci17902
|View full text |Cite
|
Sign up to set email alerts
|

HGF, SDF-1, and MMP-9 are involved in stress-induced human CD34+ stem cell recruitment to the liver

Abstract: Hematopoietic stem cells rarely contribute to hepatic regeneration, however, the mechanisms governing their homing to the liver, which is a crucial first step, are poorly understood. The chemokine stromal cell-derived factor-1 (SDF-1), which attracts human and murine progenitors, is expressed by liver bile duct epithelium. Neutralization of the SDF-1 receptor CXCR4 abolished homing and engraftment of the murine liver by human CD34 + hematopoietic progenitors, while local injection of human SDF-1 increased thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
350
4
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 547 publications
(387 citation statements)
references
References 49 publications
27
350
4
6
Order By: Relevance
“…These factors are particularly important for regulating stem cell activities such as mobilization, proliferation, and differentiation. 20,21,[25][26][27][28] More importantly, some of these signals are only transiently activated at the early stage of injury and usually diminish by day 10 after injury. 7,20,21,25,29 In the present study, we have demonstrated that there was limited blood chimerism 3 days after parabiotic surgery, and that the crosscirculatory system required 7 to 10 days to be fully established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These factors are particularly important for regulating stem cell activities such as mobilization, proliferation, and differentiation. 20,21,[25][26][27][28] More importantly, some of these signals are only transiently activated at the early stage of injury and usually diminish by day 10 after injury. 7,20,21,25,29 In the present study, we have demonstrated that there was limited blood chimerism 3 days after parabiotic surgery, and that the crosscirculatory system required 7 to 10 days to be fully established.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike bone marrow transplantation, parabiosis requires additional time for the cross-circulatory system to be developed in the animals. 19 Because injury-induced signals are important modulators of stem cell activities and are only transiently elevated at the early stage of injury, [20][21][22] we hypothesized that contribution of bone marrowborne circulating cells to cardiac repair may only be observed when cross-circulation has already been established at the time of injury. To test this hypothesis, in this study, the fate of circulating bone marrow cells in the injured myocardium was re-evaluated by subjecting parabiotic mice to surgery-induced myocardial infarction (MI) only after peripheral circulation had been stabilized.…”
Section: Editorial See P 563 In This Issue See P 551mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data suggest that such a population of resident primitive non-hematopoietic stem cells in the BM might play an important role in the repair of solid organs and turnover of tissue-resident stem cells, such as CSC. Such a mechanism requires the rapid mobilization of these cells from the BM into peripheral blood after tissue injury and their efficient homing and retention [12,13,14,15,16].…”
Section: Bone Marrow-derived Stem Cellsmentioning
confidence: 99%
“…HSCs and non-HSCs are actively chemoattracted by factors secreted by BM stroma cells and osteoblasts (e.g., stromal derived factor-1, SDF-1; hepatocyte growth factor, HGF), and colonize BM by the end of the second and the beginning of the third trimester of gestation Kucia et al 2005a;Kucia et al 2005b;Kucia et al 2005c;Kucia et al 2006a;Kucia et al 2006b;Kucia et al 2006d;Ratajczak et al 2003;Ratajczak et al 2004). Accumulating evidence suggests that these non-HSCs residing in BM play some role in the homeostasis/turnover of peripheral tissues and, if needed, could be released/mobilized from BM into circulation during tissue injury and stress, facilitating the regeneration of damaged organs (Abbott et al 2004;Gomperts et al 2006;Kale et al 2003;Kollet et al 2003;Kucia et al 2004;Kucia et al 2006c;LaBarge et al 2002;Long et al 2005;Wojakowski et al 2004). …”
Section: Introductionmentioning
confidence: 99%